Topological control of laser-driven acceleration structure for producing extremely bright ion beams. (21st April 2021) - Ju, L.B.; Huang, T.W.; Li, R.; Jiang, K.; Wu, C.N.; Zhang, H.; Wu, S.Z.; Yu, M.Y.; Qiao, B.; Zhu, S.P.; Zhou, C.T.; Ruan, S.C.
Abstract: We propose to use intense optical vortex to control laser-based ion acceleration for obtaining high-quality ion beams. An acceleration field favorable for generating well-collimated energetic proton beams results from the interaction of a tailored vortex laser pulse with thin solid-density foil in a blowout regime. Three-dimensional particle-in-cell simulations show that the foil protons can be efficiently accelerated to the GeV level in the form of a beam with small radius (<1  μ m), narrow divergence (<0.1 rad), and low emittance (∼0.004 π mm mrad). The proton beam is of high energy density (>10 18 J m −3 ) and high brightness (>10 22 A m −2 rad −2 ), exceeding that of the Gaussian laser case by four orders of magnitude, and the energy conversion efficiency is about 12 times that under the same laser intensity. The scheme can also be used to accelerate heavier, such as carbon, ions. The resulting ion beams should be useful as compact neutron source, for creation of warm dense matters, as well as ion-beam direct and indirect drive inertial confinement fusion, ultrafast diagnostics of the implosion dynamics in the latter, etc.